School mathematics as context: examining discourses about the subject in district policymaking - Nguyen, Phi (Educational studies in mathematics, 2024)
School subjects differ in their histories, epistemologies, and relations to state and federal policies. Though educational policymaking is shaped by how education leaders view school mathematics—what mathematics is, how mathematics is learned, and what counts as equitable and high-quality mathematics education—policy research often takes a subject-neutral perspective, ignoring the ways in which policymaking is rooted in the subject-matter. In this article, I report the ways in which systems of meaning or discourses about school mathematics penetrate the policymaking of two school districts. Based on a discourse analysis of interviews, observations, and artifacts, I found five main discourses about school mathematics reflected in district policymaking: (1) mathematics is a core school subject; (2) mathematics is sequential , where mastery of prior learning is necessary for future learning; (3) mathematics is well-defined , with agreement over the content; (4) there are competing perspectives of high-quality mathematics pedagogy, between conceptually-oriented instruction and direct instruction focused on procedures; and (5) equity in mathematics is access and achievement. These discourses about school mathematics were written in formal policy texts, institutionalized in district-wide practices for assessment, intervention, and tracking, and reflected in leaders’ personal views and social narratives from teachers, parents, and the community. By making visible the taken-for-granted meanings about school mathematics shaping educational policymaking, it becomes possible to interrupt and challenge them with alternative discourses.